INTERNATIONAL LAW INTERNATIONS AND HUMAN RIGHTS - Saleh Raed Shatat (UNISSULA, 2019)
International law, also known as public international law and law of the nation is the set of rules, norms, and standards generally accepted in relations between nations. The sources of international law include international custom (general state practice accepted as law), treaties, and general principles of lawrecognized by most national legal systems. Human Rights are the basic rights and freedoms to which all human beings are entitled, like civil and politicalrights, the right to life and liberty, freedom of thought and speech/expression, equality before the law, social, cultural and economic rights, the right to food,the right to work, and the right to education. In short, human rights are freedoms established by custom or international agreements that protect the interests of humans and the conduct of governments in every nation. Human rights are distinct from civil liberties, which are freedoms established by the lawof a particular state and applied by that state in its own jurisdiction. Human rights laws have been defined by international conventions, by treaties, and by organizations, particularly the United Nations. These laws prohibit practices such as torture, slavery, summary execution without trial, and arbitrarydetention or exile.